Vulnerabilidade e riscos geomorfológicos e hidrológicos na região da grande Aracaju - Santos, Alizete dos (2019)
The process of urbanization in Brazil has been characterized by the rapid and disordered way of stimulating the occupation of dwellings in environments physically vulnerable to the use and occupation of the soil. This dynamic undoubtedly places the population of low purchasing power in situations of exposure to environmental risks, be they geomorphological and / or hydrological. The Greater Aracaju Region, an area of this scientific research, in the last three decades, has been showing high rates of urban growth. Allied to this, the process of slackening and socio-spatial segregation has been one of the representations of social vulnerability to environmental events. In this sense, it was prioritized as a general objective, to analyze the areas of vulnerability and hydrological and geomorphological environmental risks in the municipalities of the Greater Aracaju Region. Thus, in order to fulfill this and other specific objectives outlined here, different methodological procedures were used, associated with different phases, such as bibliographical, cartographic and fieldwork surveys. Among the results obtained, it was verified that the social vulnerability in the referred region presents evident inequalities, not only among the municipalities, but also within them. Aracaju, capital of the state, presents concentration of wealth and better indicators in the area of access to education and income, but the pattern of occupation and slum dwelling in its periphery, weighed significantly in determining the index of social vulnerability, framed as very high , whose situation resembles that of the municipality of Nossa Senhora do Socorro. In spite of the hydrological events, it was verified that in the Greater Aracaju Region they are more frequent to the detriment of the geomorphological risks, manifested punctually in certain portions of the territory of Greater Aracaju, where they have their greater occurrences in the municipalities of Aracaju, São Cristóvão and Maruim. In order to spatialize the occurrence of these events, we sought support in Digital Cartography and Geoprocessing to elaborate two important thematic charts of susceptibility to hydrological risks (floods and floods) and geomorphological risks (mass gravitational movements and erosion). Therefore, there is an urgent need for investments in scientific research that discuss thematic, education and planning in the field of prevention, mitigation and actions after the occurrence of natural disasters.